(untitled) (Journal of Enam Medical College, 2013)
Leprosy (Hansens disease) is a chronic granulomatous infectious disease that primarily affects the peripheral nerves, skin, upper respiratory tract mucosa, eyes and certain other tissues. It is diagnosable and curable if recognized early and treated adequately. A twenty nine-year-old male from Jessore, Bangladesh reported in Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh with the complaints of multiple erythematous, large, raised and circumscribed lesions with loss of sensations on different parts of the body, especially distal portions of all four limbs for last eight months. Subsequently he developed ulcers on the anesthetic fingers due to smoking and few ulcerative lesions on both feet. Skin examination revealed multiple erythematous, large nodular lesions on both sides of the cheek and forehead, multiple erythematous, indurated, large plaques with raised margin and central clearing on the trunk, waist and all four limbs, few satellite lesions around the large plaques on the trunk, few hypopigmented patches and plaques on buttock and lower limbs, multiple painless ulcers on dorsal surface of fingers of both hands, both lateral malleoluses and right sole. On examination of peripheral nerves, left great auricular nerve, both ulnar nerves and both common peroneal nerves were moderately enlarged and tender. Slit skin smear for AFB (modified Z-N stain) was done and revealed that there were large number of acid and alcohol-fast bacilli arranged in straight and curved parallel bundles with globular masses (cigar-bundle appearance), morphologically resembling Mycobacterium leprae. Skin biopsy for histopathological examination revealed extensive infiltration of macrophages in the dermis, separated from epidermis by narrow grenz zone, with destruction of skin adnexa. Few foci of poorly defined granuloma in dermis were also noted. The patient was managed with rifampicin, clofazimine, dapsone, prednisolone and omeprazole. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 109-112 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16134